Leptin, blood pressure, and left ventricular mass in obese adolescents - David Kaunang; Handri Widodo; Vivekenanda Pateda (Indonesian Pediatric Society, 2013)
Background Obesity is characterized by an excessive accumulationof body fat and has become a major health problem in industrializedsocieties especially with regards to heart disease. Adipose tissuederived hormone (leptin) can cause obesity. Leptin acts to reducefood consumption and enhance energy expenditure.Objective To assess for a relationship between leptin, bloodpressure, and left ventricular mass in obese adolescents.Methods This was a cross-sectional study conducted fromNovember 2011 to April 2012 in Prof. Dr. RD. Kandou Hospital.This study included obese and healthy adolescents aged 13-18years who attended school in Tuminting District ofManado. Eachsubject underwent measurements of body mass index (BMI), booldpressure, and plasma leptin level. Correlation regression test wasused for data analysis. Results were considered to be statisticallysignificant if P values < 0.05.Results There was a significant relationship between leptin andleft ventricular mass (r=-0.467; P=0.006), as well as leptin andsystolic blood pressure (r=-0.366; P=0.028), but not betweenleptin and diastolic blood pressure (r=-0.261; P=0.09). We alsofound significant relationships between systolic blood pressure andleft ventricular mass (r=0.724; P<0.001), and between diastolicblood pressure and left ventricular mass ( r=0.615; P< 0.001) inobese adolescents.Conclusion Higher leptin levels are associated with lower leftventricular mass and lower systolic blood pressure, but are notassociated with diastolic blood pressure.